Pengaruh Pemberdayaan Karyawan dan Kerjasama Tim terhadap OCB dengan Kepuasan Kerja sebagai Variabel Intervening pada PT BPR Bank Jombang Perseroda - Kristin, Asbari Nurpatria; Mujanah, Siti; Fianto, Achmad Yanu Alif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
One of the things that can increase Organizational Citizenship Behaviour (OCB) is employee job satisfaction. This study investigates the effect of employee empowerment and teamwork on employee satisfaction. It also investigates whether employee satisfaction is a good mediator. This study surveyed employees at PT BPR Bank Jombang Perseroda. Using saturated sampling method, 96 employees were surveyed. Data was then analysed using Structural Equation Modelling. The findings show that employee empowerment and teamwork contribute positively to employee satisfaction. The study also proved that employee satisfaction mediates the relationship of employee empowerment and teamwork to OCB. This study contributes to understanding employee behaviour using the framework of employee satisfaction and OCB in PT BPR Bank Jombang Perseroda, which can also be applied to other public companies